2003
DOI: 10.1080/0264041031000101980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of focus of attention depend on golfers' skill

Abstract: In this study, we examined the influence of internal and external attention instructions on the performance of a pitch shot by golfers who were either highly skilled (mean handicap = 4) or low skilled (mean handicap = 26). Ten golfers in each skill group used a 9-iron to pitch a ball as close as possible to an orange pylon, which was located at distances of 10, 15, 20 or 25 m from the golfer. Focus of attention was manipulated within participants (counterbalanced across golfers). Under internal focus of attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
3
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(150 citation statements)
references
References 17 publications
10
125
3
12
Order By: Relevance
“…Consistent with this view, found that requiring experienced golfers to attend to a specific component of their swing impaired their performance in a putting task. Novices, by contrast, benefit from focusing attention on elements of skill execution or the internal production of movement (Perkins-Ceccato, Passmore, & Lee, 2003; but see Wulf & Su, 2007). These examples all involve attention to a skill during its execution, however; it is unclear whether simply thinking verbally about a skill offline disrupts later skilled performance.…”
Section: The Present Experimentsmentioning
confidence: 99%
“…Consistent with this view, found that requiring experienced golfers to attend to a specific component of their swing impaired their performance in a putting task. Novices, by contrast, benefit from focusing attention on elements of skill execution or the internal production of movement (Perkins-Ceccato, Passmore, & Lee, 2003; but see Wulf & Su, 2007). These examples all involve attention to a skill during its execution, however; it is unclear whether simply thinking verbally about a skill offline disrupts later skilled performance.…”
Section: The Present Experimentsmentioning
confidence: 99%
“…As diferenças significativas observadas foram somente entre as avaliações, especificamente do PRÉ para o PÓS2 (F (1,53) = 51.21, p < .01), do PRÉ para a RET (F (1,53) = 47.96, p < .01), do PÓS1 para o PÓS2 (F (1,53) = 47.19, p < .01) e do PÓS1 para a RET (F (1,53) = 46.41, p < .01). (Perkins-Ceccato et al, 2003;Poolton et al, 2006;Wulf et al, 1998Wulf et al, , 2002Wulf & Su, 2007). Conforme os achados, direcionando a atenção para um foco externo os aprendizes utilizam um tipo de controle automático da ação, diferentemente de quando eles direcionam a atenção para o movimento do seu corpo de forma consciente, o que tende a degradar a performance (Poolton et al, 2006).…”
Section: A B C D -Diferenças Entre As Avaliações (P < 05)unclassified
“…In the last few years, investigation on the performance and learning of motor skills has focused on the internal (i.e., movement patterns) and external (i.e., environmental characteristics) aspects of a task [7]. The results of this body of research have highlighted the superiority of external focus of attention on the performance and learning of motor skills in comparison to those based on internal focus and control (no attentional focus) [5,[8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%